The Identity Dimension of the Yi-An Style: The Value System of Li Qingzhao - Dashchenko, Anna (Respectus Philologicus, 2013)
This article is devoted to revealing the identity dimension of the Yi-an style, i.e., the aggregate of the value system of Song poetess Li Qingzhao (1084–1155) becoming apparent in the idea and image content of her ci in such a way that her poems appear to be written by male authors. The empirical material for this research consists of 41 ci, whose authorship is beyond question according to most scientists. These poems were divided into three periods: Youth or Pre-marriage (1099–1101), Marriage (1101–1127), and After the fall of the dynasty and her husband’s death (1127–1155). A hypothesis was made, according to which Li Qingzhao’s works are characterized by traditionally “masculine” values, namely: a) the absolute primacy of scholarship and literary activities in the whole, and b) an emphasis on the transcendental, particularly on immaterial wealth. This hypothesis was tested by applying the chromatic scale to Li Qingzhao’s ci. Poems containing yellow, green, and black colors, and “achromic” ci, were analyzed. This allowed a demonstration of how her highly intimate feelings are embedded in general cosmological and ontological contexts. In particular, the yellow-golden spectrum of Li Qingzhao’s ci reveals the absolute priority of immaterial or intellectual wealth. A blue-green spectrum shows the process of understanding the Self, the value of her own identity, and striving for being, as remembered by performing the typically “male” activity of writing. Black reveals an emphasis on the transcendental, and the increasing number of “achromic” ci toward the end of her life was a strategy for Li Qingzhao to emphasize the process of understanding the self.
Keywords: Li Qingzhao; Ci; Identity Dimension; Yi-An Style; Chromatic Scale; Range of Colors; “Achromic” Ci